iid2022: a workshop on statistical methods for event data in astronomy - Feigelson, Eric D.; Bonamente, Massimiliano (Frontiers in Astronomy and Space Sciences, 2023)
We review the iid2022 workshop on statistical methods for X-ray and γ-ray astronomy and high–energy astrophysics event data in astronomy, held in Guntersville, AL, on Nov. 15–18 2022. New methods for faint source detection, spatial point processes, variability and spectral analysis, and machine learning are discussed. Ideas for future developments of advanced methodology are shared.